New findings on seed ecology of Ribes sardoum: can it provide a new opportunity to prevent the extinction of a threatened plant species?. Issue 5 (3rd September 2017) - Porceddu, Marco; Fenu, Giuseppe; Bacchetta, Gianluigi
Abstract : Ribes sardoum, the most threatened endemic plant of Sardinia, is included in the Habitats Directive (92/43/EEC) and it was considered Critically Endangered in the global IUCN Red Lists. This species has been reported to have an extremely low fertility, scarce fruit production, low seed viability and a general inability to reproduce sexually. Fruits were collected for the first time from the remnant population, and the requirements for seed germination were investigated in the laboratory. Seeds were incubated at different temperatures (10, 15, and 20°C) and, in addition, they were exposed to a warm stratification (W) or a move-along treatment characterized by three cold temperature regimes (CCC). Seeds were also sown on the surface of 1% agar water with 250 mg·L −1 of GA3 . At maturity, seeds have a linear underdeveloped embryo. Germination percentage between 35% and 65% were detected in the control and W groups. A low germination percentage occurred after CCC and during GA3 treatment. W treatment speeds up seed germination. Our results demonstrate that fruits of R. sardoum produce viable seeds, that are able to germinate under controlled conditions, with the assumption that the seeds have morphophysiological dormancy (MPD), and that propagation from the seeds is possible. Although the ability of seed germination was demonstrated, the lack of seedlings in the natural population seems to be a consequence of unfavourable climatic conditions for recruitment. However, our results indicate that seedlings obtained under controlled conditions could be useful for future translocation reducing and/or mitigating the extinction likelihood of this highly threatened plant.